ANALISIS KINERJA BIROKRASI POS PAUD TERPADU MELATI KECAMATAN SUKOLILO KOTA SURABAYA - Faridah, Aisiah Cici; Febriani, Vania Indah; Musleh, Moh (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This study aims to analyze the bureaucratic performance of the Integrated Early Childhood Education Post Melati Sukolilo District in Surabaya. The research was conducted using descriptive qualitative research methods. Data collection techniques, namely interviews, observation, and documentation. Data analysis techniques were carried out according to the Miles and Habermann data analysis model. In assessing the performance of the bureaucracy at the Melati Integrated Early Childhood Education Post, this study uses five indicators in measuring bureaucratic performance according to Agus Dwiyanto, namely productivity, service quality, responsiveness, responsibility, and accountability. The results showed that the performance of the bureaucracy at the Melati Integrated Early Childhood Education Post had been carried out quite well by measuring the five indicators put forward by Agus Dwiyanto. There are several supporting factors in the form of digital government and financial assistance from the Regional Budget that can improve bureaucratic performance and inhibiting factors in the form of lack of adequate facilities, infrastructure, and transportation problems that can reduce bureaucratic performance, with the existence of these factors can be a measurement of high or low bureaucratic performance.